Evaluation of the genotoxicity of waters impacted by domestic and industrial effluents of a highly industrialized region of So Paulo State, Brazil, by the comet assay in HTC cells - Manzano, Barbara Cassu [UNESP]; Roberto, Matheus Mantuanelli [UNESP]; Hoshina, Marcia Miyuki [UNESP]; Menegario, Amauri Antonio [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Springer, 2015)
The problems that most affect the quality of the waters of rivers and lakes are associated with the discharges performed in these environments, mainly industrial and domestic effluents inappropriately treated or untreated. The comet assay is a sensitive tool and is recommended for studies of environmental biomonitoring, which aim to determine the genotoxicity potential of water pollutants. This study aimed to assess the genotoxic potential of the Ribeiro Tatu waters, region of Limeira, So Paulo (SP), by the comet assay with mammalian cells (hepatoma tissue culture (HTC)). Water samples were collected along the Ribeiro Tatu at three distinct periods: November 2008, February 2009 and August 2009, and five collection sites were established: P1, source of the stream; P2, site located downstream the urban perimeter of the municipality of Cordeirpolis and after receiving the pollution load of this city; P3, collection site located upstream the urban perimeter of the city of Limeira; P4, urban area of Limeira; and P5, rural area of Limeira, downstream the discharges of the city sewage. The results showed that for the November 2008 collection, there was no water sample-induced genotoxicity; for the February 2009 collection, the sites P1 and P2 were statistically significant in relation to the negative control (NC), and for the August 2009 collection, the site P5 was statistically significant. These results could be explained by the content of different metals during the different seasons that are under the influence of domestic, industrial and agricultural effluents and also due to the seasonality, since the water samples collected in the period of heavy rain (February 2009) presented a higher genotoxicity possibly due to the entrainment of contaminants into the bed of the stream promoted by the outflow of rainwaters. The comet assay showed to be a useful and sensitive tool in the evaluation of hydric resources impacted by pollutants of diverse origins, and a constant monitoring should be done in order to verify the influence of different factors (season, amount of contaminants) in the water quality.
Keywords: Contamination of hydric resources; HTC cells; Comet assay; Environmental biomonitoring; Domestic effluents; Industrial effluents